FYP Online Marking System (FOMS) - Abdul, Nor Atika (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Final Year Project (FYP) is one of the compulsory courses that need to be taken by all of the final year students. In UTP, FYP course is available in two semesters, namely FYP1 and FYP2 respectively. For each of the courses, the FYP students need to submit several deliverables in order to complete their coursework. These deliverables will be evaluated by the students’ supervisor and the panel of examiners. The FYP marking process in UTP is still manually implemented. This means that the supervisor and the panel of examiner manually write down the students information and the awarded mark for the students in a paper-based score sheet. The manual FYP marking process causes a lot of problem to the supervisor and the panel of examiners as well as the FYP coordinators, who administrator the FYP course. Among of the problems identified are inefficiency and error-likely of FYP manual marking process, unorganized and time-consuming of FYP oral presentation and paper wastage and confidential issue. Therefore, the implementation of FYP Online Marking System is vital with the objectives to convert the manual FYP marking process into an automated FYP online marking system, to increase the process efficiency and reduce the possible error chances, to have a more organized and time-saving FYP marking process flow, to go green and help to preserve the environment. The scopes that the FOMS project covers include FYP marking process out of the overall FYP course process and the CIS department’s lecturer and panel of examiners as the main user. The FOMS system implementation covers for both of the FYP1 and FYP2 courses. In order to complete the FOMS system, prototyping will be the methodology used as it allows the project analysis, design and implementation to be done concurrently and repeatedly until complete. A set of survey has been done to gather the feedback on the current manual FYP marking process and their opinion on FOMS. An acceptance test has also been carry out to gather feedback related to the FOMS system.